Measuring the maturity of the business intelligence and analytics initiative of a large Norwegian university - Su, X.; Cardoso, E. (International Journal of Business Intelligence Research, 2021)
Maturity models of Business Intelligence and Analytics (BIA) have been previously used to assess BIA development progress in organizations in many sectors, such as healthcare and business. However, there is a lack of studies reporting up-to-date knowledge on applying maturity assessment in Higher Education Institutions (HEI). It remains unclear precisely to what extent and how HEI employ maturity assessment and the benefits of such exercises. This paper addresses this gap by reporting a case study at a large Norwegian university. A domain-specific maturity model is used as a lens to observe and reflect on the BIA implementation at the Norwegian University of Science and Technology. This paper reports the assessment results and discusses the implications of the maturity assessment. The findings and discussions in the case can cater to a broader audience of BIA practitioners and researchers, contributing to understanding the value and adoption dynamics of BIA in Higher Education.